Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

cubed root of (-8x^9).... I have -2x^?

See more answers at
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer


To see the expert answer you'll need to create a free account at Brainly

(-8x^9)^1/3 =-2x^3
so you just take the square root of the nine

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

take the cube root of -8 that is -2 and the x power of 9 divided by 1/3 power=3
oh ok thank you
i mean multiplied by 1/3 or divided by 3
so what do you do if it says the cubed root of say 2? what is that then?
ok cube root of 2=2^(1/3) if you use a calculator =1.2599
ok thanks I'm not really sure how to do this hw I have lol so Im just trying to piece it all together thank you!
1.2599(1,2599)(1.2599)=1.2599^3 =2
a god example is cube root of -8 that is (-8)^1/3=-2 to check this (-2)x(-2)x(-2)=-8
(-2)(-2)(-2)= (-2)^3=-8 this is a cubed of -2,,, now its reversed is the cube root cube root of -8=(-8)^(1/3) =-2
if (-b)^1/3=-a then (-a)^3=-b
right ok
algebraically,,,,if (-b)^1/3=-a here lets put both sides to the power of 3 [ (-b)^1/3 ]^3=[-a]^3 [ (-b)^3/3 ]=[-a]^3 [ (-b)^1 ]=[-a]^3
good luck now

Not the answer you are looking for?

Search for more explanations.

Ask your own question